The grumpy gardener : an A to Z guide from the galaxy's most irritable green thumb - Bender, Steve (New York, NY : Oxmoor House, 2017)
Gardeners from across the country have turned to Southern Living Senior Garden Editor Steven Bender - known affectionately as "The Grumpy Gardener"--For his keen knowledge and gardening know-how with equal doses sarcasm and sidesplitting humor for nearly 35 years. Finally, the collected wit and wisdom of the magazine's most irreverent and beloved columnist can be found in a single A - Z volume, providing gardeners from coast-to-coast with his valuable tips for planting, troubleshooting, and growing flowers, vegetables, shrubs, trees and more, all delivered in his signature cantankerous style. Sidebars throughout the book - "Ask Grumpy"--help readers tackle common garden problems ("How do I get ride of little house ants?"), and readers from the past 35 years take part in the book when Grumpy shares his favorite reader's responses to some of his advice, his favorite rules for gardening, and Q & A's covering your favorite plants and flowers are all inside. Additionally, beautiful line-drawings and illustrations throughout make the book as beautiful to look at as well as entertaining to read. The Grumpy Gardener is sure to become the most trusted tool in your gardening shed!--
Includes index.
Keywords: Gardening; Gardening; GARDENING -- Container; Gardening